Single vs. combination immunotherapeutic strategies for glioma - Chandran, Mayuri (2017)
Introduction: Malignant gliomas are highly invasive tumors, associated with a dismal survival rate despite standard of care, which includes surgical resection, radiotherapy and chemotherapy with temozolomide (TMZ). Precision immunotherapies or combinations of immunotherapies that target unique tumor-specific features may substantially improve upon existing treatments. Areas covered: Clinical trials of single immunotherapies have shown therapeutic potential in high-grade glioma patients, and emerging preclinical studies indicate that combinations of immunotherapies may be more effective than monotherapies. In this review, the authors discuss emerging combinations of immunotherapies and compare efficacy of single vs. combined therapies tested in preclinical brain tumor models. Expert opinion: Malignant gliomas are characterized by a number of factors which may limit the success of single immunotherapies including inter-tumor and intra-tumor heterogeneity, intrinsic resistance to traditional therapies, immunosuppression, and immune selection for tumor cells with low antigenicity. Combination of therapies which target multiple aspects of tumor physiology are likely to be more effective than single therapies. While a limited number of combination immunotherapies are described which are currently being tested in preclinical and clinical studies, the field is expanding at an astounding rate, and endless combinations remain open for exploration.